Evaluate the enantioselective behavior of ethiprole: Implications for aquatic systems health and human safety - Chao Zhu; Mingyue Pang; Wenwen Gong; Hengming Pang; Han Qu (Emerging Contaminants)
Increasing numbers of chiral insecticides have been released into aquatic environments, leading to adverse effects on the environment. Furthermore, these insecticides have potentially undesirable side effects on the environment, humans and other non-target species, potentially disrupting entire ecosystems. This study investigated the effects of ethiprole enantiomers against microorganisms in sediment, duckweed, and human cells. The results showed that S-ethiprole degraded preferentially in sediment, demonstrating enantioselective behavior. In sediment, catalase and superoxide dismutase activities were significantly inhibited, and the frond number of duckweed preferably decreased with exposure to S-ethiprole at high concentration treatments (33 : 25 = R-ethiprole: S-ethiprole). Additionally, the content of chlorophyll b decreased nearly 2 times in R-ethiprole (0.42 mg/g) treatment group in comparison to S-ethiprole (0.20 mg/g) treatment. Cytotoxicity test revealed that S-ethiprole was 2 and 3 times more toxic than rac- and R-ethiprole. The expressions of CAT, SOD and caspase-3 were up-regulated in human cells treated with ethiprole enantiomers, indicating oxidative stress as a key factor in toxicity. Overall, S-ethiprole exhibited greater adverse effects than rac- and R-enantiomers in human cells. These findings demonstrate the importance of considering chirality in the risk assessment of harmful chemicals in the aquatic environment.